PTCy BMT for RDEB. (3rd December 2019) - Ebens, C.L.; McGrath, J.A.; Tamai, K.; Hovnanian, A.; Wagner, J.E.; Riddle, M.J.; Keene, D.R.; DeFor, T.E.; Tryon, R.; Chen, M.; Woodley, D.T.; Hook, K.; et al.
Summary: Generalised severe recessive dystrophic epidermolysis bullosa (RDEB‐GS) is a rare, incurable genetic disorder in which an essential skin component, type 7 collagen (C7), is defective or missing. As a result, skin and mucous membranes detach from the body, causing blisters and wounds. Bone marrow transplantation (BMT) can restore C7 in the skin, probably by supplying mesenchymal stem cells (MSCs) which turn into healthy new skin cells. However, BMT is a risky and unpleasant procedure because the drugs needed to stop the patient's immune system rejecting the donated bone marrow can themselves cause illness and sometimes death. Immune cells in the transplanted tissue may even attack the patient, causing graft versus host disease (GvHD). These doctors at the University of Minnesota tried a different BMT protocol in 10 children with RDEB‐GS, using less intense immune‐suppression pre‐transplant. Three days post‐transplant they gave an immunosuppressive drug called cyclophosphamide (PTCy). Two months later, when the patient's body had accepted the donor tissue, they were able to give more MSCs from the same donor. The graft failed in three patients, two of whom underwent repeat BMT followed in one by severe complications and death a year later. Successfully transplanted patients tended to show more C7 in their skin biopsies and improved symptoms with reductions in itch, pain and areas of blistered skin. None suffered GvHD in the short term. The authors conclude that PTCy BMT is feasible in people with RDEB‐GS, even with "less‐than‐perfectly‐matched" donors, and allows repeat "top‐up" MSC grafts from the same donor. Abstract : Linked Article:  Ebens et al. Br J Dermatol 2019; 181 :1238–1246